Calf growth experiment - Interim report - Donaldson, T.J. (International Livestock Centre for Africa, 1984)
Presents preliminary results of a study on mortality & growth rates of Boran calves given mineral supplements & a health package, feed supplement only or feed & mineral supplements and a health package in Ethiopia.